PTU-051 Diagnostic yield of oesophago-gastro-duodenoscopy as the initial investigation for patients presenting with haematochezia. (22nd June 2015) - Boyd-Carson, H; Ishaq, S; Disney, BR
Abstract : Introduction: It is suggested that 15% of patients presenting with haematochezia will have an upper gastrointestinal (UGI) source of bleeding. 1 Current surgical school of thought recommends oesophago-gastro-duodenoscopy (OGD) as first-line investigation for patients with haematochezia. 2 More recent thinking suggests that a nasogastric lavage should be undertaken in this patient group to identify an UGI source of bleed. 2 We aimed to investigate whether the reported figure was an accurate representation and whether OGD should be undertaken primarily. Method: Patients who presented with haematochezia were identified between January 2010 and June 2014, using clinical coding. Data collected included demographics, presentation, initial haemoglobin and urea serum levels, OGD findings and results from further endoscopic investigation. Results: A total of 231 patients were identified (mean age 68 years, 55% male). Of these, 42 underwent OGD as first-line investigation. The majority of these (73%) had a normal endoscopy. The following pathologies where identified in the remaining endoscopies; duodenitis (7%), gastric ulcer (4%), gastritis (2.3%), oesophagitis (2.3%), oesophageal telangiectasia (2.3%), gastric erosions (2.3%), oesophageal ulcer (2.3%) and oesophageal varices (2.3%) Of those with a normal OGD, 80% had a further lower GI endoscopy. 60% of these patients had a clear LGI pathology accounting for their presentation. These findings demonstrate that of the patients who underwent OGD first line, only 7% had significant UGI pathology at OGD (peptic ulcer, oesophageal varices) with 2% actively bleeding (oesophageal varices). The mean haemaglobin for this population was 98 g/L (range 32–142 g/L). The median serum urea level was 9.2 mmol/L (range 1–13.2 mmol/L). In those with a normal OGD, 35% had a raised serum urea (mean 8.3 mmol/L, range 1.0–46.2 mmol/L). Whilst in those with an identified attributable UGI pathology, serum urea was raised in 100% of the cases (mean 8.8 mg/dl, range 7.9–9.9 mg/dl.) Conclusion: We suggest an incidence of UGI pathology leading to haematochezia of 7%, which is far lower that the quoted figure of 15%. We therefore challenge surgical recommendation that OGD should be the first line investigation in this patient group unless haemodynamic instability or clinical suspicion is suggestive. Disclosure of interest: None Declared. References: Jensen DM, Machicado GA. Diagnosis and treatment of severe hematochezia. The role of urgent colonoscopy after purge. Gastroenterology 1988;95(6):1569–74 Jensen DM, Ghassemi KA. Lower GI Bleeding: epidemiology and management. Curr Gastroenterol Rep. 2013;15(7):333